THE EFFECT OF FINANCIAL RATIOS ON STOCK RETURN STUDY ON FOOD AND BEVERAGES COMPANIES LISTED ON INDONESIA STOCK EXCHANGE DURING 2015-2017 - Rina Ani Sapariyah; Genia Oktri Chrisandana (ADVANCE, 2019)
This study aimed to discover and provide and empirical evidence of significance of Current Ratio (CR), Earning per share (EPS), and Total assets turnover (TAT) to Stock Return. Population in this study consist 21 Food andBeverages companies listed on  Indonesia Stock Exchange in the observation of 2015-2017 with as the samplingmethod wich contains 13 Food and Beverages companies. The methods of analysis used are classic assumption test,multiple linear regression analysis, t test and R2 test. The result of classic assumption that contains normality test showsthat the data has been normally distributed, multicollinearity test shows that there is no multicollinearity between theindependent data and dependent data, heteroscedasticity test shows that there is no heteroscedasticity in this data, andautocorrelation test shows that there is no autocorrelation in the regression of this study. The result of hypothesis testingshows Earning per share and Total assets turnover has positive effect but non significant to Stock Return. CurrentRatio has negative effect and not significant to Stock Return. The coefficient of determination result shows that CurrentRatio, Earning per share and Total assets turnover has 6,6% effects to Stock Return, and the rest 93,4% influenced byother variables that not researched.